Analysis and proposals for the system of support and safeguards for people with disabilities who cannot manifest their will - Espinal Quiñones, Aveghai Mirella (2023)
Legislative Decree n.° 1384 «Legislative Decree that recognizes and regulates the legal capacity of people with disabilities on equal terms» published on September 4, 2018 brought with it a strong impact on the capacity system regulated by the Peruvian Civil Code, it modified, repealed and incorporated a series of articles into our legislation, thus producing the largest and far-reaching reform of the 1984 civil code. all with the aim of having a new capacity system. However, in the opinion of the authors, said reform has not been correctly adapted to our legislation, considering that people who do not have discernment are being left helpless, for granting them such a special attribute that is full exercise capacity, which did not happen before the reform of the Civil Code, for this reason proposals and possible solutions to such an important situation are presented, in order to provide the most appropriate protection to all people with disabilities who cannot express their will.